2021
DOI: 10.1029/2020jb020967
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crystal Elasticity of MgSiO3 Bridgmanite to Mid‐Lower Mantle Pressure

Abstract: While it is accepted that the lower mantle phase assemblage is comprised primarily of Al-and Fe-bearing MgSiO 3 bridgmanite, the exact proportion and the bulk composition of the lower mantle as a whole remain uncertain. The abundance of bridgmanite relative to ferropericlase will be controlled by the bulk Mg/Si ratio. In a pyrolite composition, which is believed to represent the average composition of the upper mantle (Ringwood, 1962), this ratio is ∼1.3 and a pyrolytic lower mantle assemblage would be compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…As the axial compressibility is particularly sensitive to non‐hydrostatic stresses, we limit our comparison with previous work only to single crystals synthesized in a multi‐anvil press and compressed in a DAC under quasi‐hydrostatic conditions. The axial compressibility scheme determined in this study is in agreement with previous static compression (Boffa Ballaran et al., 2012) and elasticity measurements (Criniti et al., 2021; Sinogeikin et al., 2004) of single‐crystal MgSiO 3 bridgmanite. For the Al‐bearing experiments, the compressibility of the c ‐axis is higher than in MgSiO 3 , as also observed for the Fe 3+ AlO 3 substitution mechanism (Boffa Ballaran et al., 2012), confirming that the Al‐Si substitution at the B site plays a critical role in determining the stiffness of this direction.…”
Section: Isothermal Equation Of State Of Al‐bearing Bridgmanitesupporting
confidence: 90%
“…As the axial compressibility is particularly sensitive to non‐hydrostatic stresses, we limit our comparison with previous work only to single crystals synthesized in a multi‐anvil press and compressed in a DAC under quasi‐hydrostatic conditions. The axial compressibility scheme determined in this study is in agreement with previous static compression (Boffa Ballaran et al., 2012) and elasticity measurements (Criniti et al., 2021; Sinogeikin et al., 2004) of single‐crystal MgSiO 3 bridgmanite. For the Al‐bearing experiments, the compressibility of the c ‐axis is higher than in MgSiO 3 , as also observed for the Fe 3+ AlO 3 substitution mechanism (Boffa Ballaran et al., 2012), confirming that the Al‐Si substitution at the B site plays a critical role in determining the stiffness of this direction.…”
Section: Isothermal Equation Of State Of Al‐bearing Bridgmanitesupporting
confidence: 90%
“…The phase fraction of ferropericlase in the pyrolite model is estimated to be ∼16% (Dorfman, 2016). While some high-pressure elasticity measurements support the pyrolite model for the composition of the lower mantle (Criniti et al, 2021), others suggest that a better match to average seismic wave speeds is obtained for a mantle composed of ∼7%-12% ferropericlase (Mashino et al, 2020;Murakami et al, 2012). In the lowermost mantle, higher sodium solubility implies that even less ferropericlase is needed to accommodate all available sodium.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain accurate and precise cij values, it is important that their correlation in the fit procedure is low. This is achieved by using two appropriate crystallographic orientations (Criniti et al, 2021). We used published cij data for Fo90 olivine (Abramson et al, 1997) Hydrous Fo90 olivine single crystals were first observed under a polarising microscope and selected based on the absence of inclusions and their sharp optical extinction.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has the advantage that all velocity data from all pressure points are used to constrain the cijs, minimizing the effect of data scattering on the calculated cijs and thus reducing their estimated uncertainties (Buchen, 2018). Even though this fitting procedure is particularly suited for very high pressure data, where some of the cijs are poorly constrained due to the lack of observations (e.g., Criniti et al, 2021), it can be applied to any high-pressure sound velocity dataset and the two procedures should yield consistent results as long as the collected data are of high quality, the high-pressure evolution of all cij is well described by a third-order finite strain EoS, and no phase transition takes place in the investigated pressure interval. Therefore, we also applied the global fit procedure to our dataset, which yielded very consistent results compared to those obtained by individual fits.…”
Section: Sound Wave Velocities Of Hydrous Fo90 Olivine and Cij Invers...mentioning
confidence: 99%